2015
DOI: 10.7764/psykhe.24.2.887
|View full text |Cite
|
Sign up to set email alerts
|

Condicionamiento Cultural del MACI: Un Examen del Sesgo de Constructo en Chile

Abstract: Este estudio fue financiado por el Fondo Nacional de Desarrollo Científico y Tecnológico de Chile (proyecto FONDECYT 1110383). La correspondencia relativa a este artículo debe ser dirigida a José L. Saiz, Departamento de Psicología, Universidad de La Frontera, Casilla 54-D, Temuco, Chile. E-mail: jose.saiz@ufrontera.cl Condicionamiento Cultural del MACI: Un Examen del Sesgo de Constructo en Chile Cultural Conditioning of the MACI: A Construct Bias Examination in ChileJosé L. Saiz, Eugenia V. Vinet y Ana Barrer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has been observed that some personality scales have a counter-theoretical behaviour (Submissive, Dramatizing, Egotistic and Conforming), where the averages obtained by adolescents from general sample are significantly higher than those obtained by adolescents from clinical sample (Hofstede et al, 2010;Saiz et al, 2015;Vinet, 2010). It has been argued that the pattern of inverse results observed could be due to cultural differences between Hispanic and American adolescents (Vinet, 2010) and we can conclude that these differences are also observed in our sample of the Spanish sample, which would be closer to the Latin American sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that some personality scales have a counter-theoretical behaviour (Submissive, Dramatizing, Egotistic and Conforming), where the averages obtained by adolescents from general sample are significantly higher than those obtained by adolescents from clinical sample (Hofstede et al, 2010;Saiz et al, 2015;Vinet, 2010). It has been argued that the pattern of inverse results observed could be due to cultural differences between Hispanic and American adolescents (Vinet, 2010) and we can conclude that these differences are also observed in our sample of the Spanish sample, which would be closer to the Latin American sample.…”
Section: Discussionmentioning
confidence: 99%
“…Some PRP have a counter-theoretical behavior (Submissive, Dramatizing, Egotistic and Conforming), where the averages obtained by adolescents from general sample are significantly higher than those obtained by adolescents from clinical sample (Saiz et al, 2015;Vinet, 20). It has been argued that the observed pattern of inverse results could be due to cultural differences between Hispanic and US adolescents (Vinet, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation